PATHOHISTOLOGICAL STUDY OF THE PANCREAS OF PREGNANT RATS WITH EXPERIMENTAL DIABETES - Naumanov Mashrabjon Maxmudovich (Scholar Express Journals, 2022)
To identify the complex histotopographic relationships of the nerve centers of the brain, a research method is very important, which would make it possible to trace the differentiation of the layers of the cortex in all seven layers of the human cerebral cortex. For which morphometric research methods were used, as V.A. Betz (1891) noted: "The lack of accurate anatomy and histology of the brain comes from the lack of a research method, a method that would combine the convenience of naked eye research and microscopic research." For successful dissection, pretreatment of the brain is of great importance, which would give the appropriate plasticity to the brain tissue.To this end, a number of methods for processing brain tissue have been proposed, but most of them have proved to be of little use for solving problems.
Keywords: rat; work; method; layer